The thinking strategist : unleashing the power of strategic management to identify, explore and solve problems - Edmondson, Vickie Cox (Emerald Publishing Limited, 2022)
The Thinking Strategist is your guide to accomplishing organizational goals, exceeding objectives, and securing the support of senior management and other key stakeholders. This much-needed new edition furthers the author's commitment to motivate and inspire confidence in individuals from traditionally excluded groups who work in deadline- and budget-driven roles in companies with highly competitive organizational cultures. Amongst the updates is a new chapter dedicated to the role that diversity, equity and inclusion plays in the strategic management process, especially during a period when DEI efforts are both valued and under attack. Ideal for business students and aspiring managers who seek to distinguish themselves as people who make success happen, The Thinking Strategist shows you how to develop the skills, confidence, business judgment, and resilience you need not only to be successful but to be a driver of decision making and problem solving. To be an expert - a thinking strategist.